Effect of Resin Cement Type and Thickness on Color Stability and Cement Translucency: An in-vitro study - Sabouhi, Mahmoud; Naziri, Babak; Sabzevari, Berahman; Bajoghli, Farshad; Fakoor, Mohammadhossein; Noorizadeh, Sarah (Galen Medical Journal, 2025)
Background: It is widely accepted that discoloration of resin cements is a common problem, especially in translucent restorations, which causes discoloration of restoration and the need for replacement. The purpose of this study was to investigate the effect of resin cement type and thickness on color stability and cement translucency. Materials and methods: The present in vitro study was conducted on 120 disc-shaped 5-mm samples in three thicknesses of 50, 100 and 150 microns within 12 groups using two light-cure resin cements (ultra-Bond and option 2) and two amine-free dual-cure resin cements (V5 and NX3) by silicone mold. All specimens were thermocycled under 8000 rpm and then the mean color and translucency were determined for all specimens. Data were analyzed using SPSS software. Results: Thermal cycle at 8000 rpm significantly increased color change (ΔE) and decreased translucency parameter (TP) in all four resin cements (P<0.001), although ΔE was clinically acceptable for all cements. (ΔE≤3.3). In addition, increased cement thickness caused an increase in ΔE and a decrease in translucency changes (ΔTP) (P <0.001). Conclusion: The resin cement type and thickness had an effect on color stability and cement translucency. The light-cure cements and new dual-cure amine-free cements had clinically acceptable color stability.